معاملة المجتمع المسلم الاندونيسي من قبل القرآن والحديث - Abdul Hakim Wahid (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
This article aims to learn how Indonesian Muslims treat the Quran and Hadith in their daily lives, and in particular to uncover the secrets of using Surat al-Duha as a means of searching for the missing things. This article was written based on the results of induction using the qualitative and descriptive approach with main sources are the results of interviews with the educator and students of the Islamic Kindergarten Institute, with other sources related to this research. This article concluded that the reason for using Surat al-Duha as a tool to search for something missing has to do with the interpretation of Surat al-Duha reinforced by the Hadith of the Prophet. And The word